2010
DOI: 10.1002/sia.3340
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo simulation study on the image resolution in scanning electron microscopy

Abstract: The resolution of the scanning electron microscope limited by the beam-sample interaction is studied by Monte Carlo simulation. The simulation model is based on the full Penn algorithm for electron inelastic scattering and the associated secondary electron generation as well as on a constructive solid geometry modeling of a complex sample structure. The line-scan profiles for gold nanoparticles of different diameters on a carbon substrate are obtained in the simulation. The gap method and contrast-to-gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Studies on the interactions between electrons and insulating materials have been reported, such as investigations on elemental diamond [61], compound SiO 2 [62,63], and polymethyl methacrylate [64]. Even in some cases, the layered structures [46,65] or particles on substrates [37,66,67] are considered; they are, nevertheless, a simple combination of conductive and/or semiconductive solids. The additive nature ofin an insulating layer between conductive materials requires a more detailed consideration of the electronic structure, and an improvement in Monte Carlo physical modeling is hence necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the interactions between electrons and insulating materials have been reported, such as investigations on elemental diamond [61], compound SiO 2 [62,63], and polymethyl methacrylate [64]. Even in some cases, the layered structures [46,65] or particles on substrates [37,66,67] are considered; they are, nevertheless, a simple combination of conductive and/or semiconductive solids. The additive nature ofin an insulating layer between conductive materials requires a more detailed consideration of the electronic structure, and an improvement in Monte Carlo physical modeling is hence necessary.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36] Simulation results were found to be in good agreement with experiments. [37][38][39][40][41][42] By combining Mott's cross section for describing the electron elastic scattering and the dielectric function for the electron inelastic scattering, we have developed and applied classic trajectory Monte Carlo (CTMC) simulation models to SEM, [43][44][45][46][47][48][49][50][51][52] AES [53][54][55][56] and reflected electron energy loss spectroscopy [57][58][59][60][61][62][63][64] with different simulation codes. 65 This CTMC simulation approach has also been applied to the analysis of thin film nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Monte Carlo simulation was also used to calculate the contrast of platinum particles in a carbon matrix when changing particle size, depth, and incident angle of the primary beam (Yue et al, 2005). The Monte Carlo simulation of scanning electron images was used to study gold nanoparticles on carbon substrates and to compare the resolution obtained with the gap and contrast-to-gradient methods (Mao & Ding, 2010). An analog image simulator, like the National Institute of Science and Technology Artimagen, is another possible method for image simulation (Cizmar et al, 2007, 2008 a , 2008 b ).…”
Section: Introductionmentioning
confidence: 99%